1999
DOI: 10.1080/00365529950172772
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Death in Patients with Peptic Ulcer Perforation: A Long-Term Follow-up Study

Abstract: Increased mortality in ulcer perforation patients could mainly be attributed to smoking-related diseases. This is indirect evidence that smoking may be an important aetiologic factor for ulcer perforation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
0
3
1
Order By: Relevance
“…Smoking was found to be strongly associated with longterm mortality, mainly due to smoking-related illnesses measured by the excessive standard mortality ratio in a previous study [6]. In the present study, smoking was not found to be significantly associated with long-term mortality in the univariate analysis.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Smoking was found to be strongly associated with longterm mortality, mainly due to smoking-related illnesses measured by the excessive standard mortality ratio in a previous study [6]. In the present study, smoking was not found to be significantly associated with long-term mortality in the univariate analysis.…”
Section: Discussioncontrasting
confidence: 70%
“…The presence of active cancer has been associated with both short‐ and long‐term mortality in patients with PPU. Indeed, the comprehensive study by Svanes et al [6] demonstrated that most causes of death in the long term were related to smoking‐associated diseases, including a high rate of cancer‐related deaths. In a more recent German study [8], age and the presence of comorbidities were also found to be risk factors for long‐term mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Svanes et al [12] assesses the causes of death in long‐term follow‐up in patients treated for peptic ulcer perforation. Ulcer perforation patients experienced increased mortality from neoplasms, lung cancer, circulatory diseases, ischemic heart disease, and respiratory diseases.…”
Section: Discussionmentioning
confidence: 99%